PENEGAKAN HUKUM TERHADAP PENGEMUDI YANG MEROKOK SAAT BERKENDARAAN BERDASARKAN UNDANG-UNDANG LALU LINTAS DAN ANGKUTAN JALAN (LLAJ) NOMOR 22 TAHUN 2009 - Mardiansyah, Agung; Sari, Indah (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2024)
“Smoking while driving is very dangerous for both the driver himself and other people, because it can interfere with concentration and cause accidents while driving. Therefore, it is very interesting and important to study further regarding how the law is enforced for drivers who smoke while driving motorized vehicles based on Law Number 22 of 2009? and what are the obstacles and efforts to overcome them in enforcing the law against drivers who smoke while driving motorized vehicles? To answer these problems, normative juridical legal research methods are used with statutory and conceptual regulatory approaches. Data obtained from primary, secondary and tertiary legal material sources were collected and then analyzed using qualitative data analysis techniques. From the research results, it was found that law enforcement against drivers who smoke while driving motorized vehicles is still low and needs to be enforced through proper implementation of traffic regulations. Obstacles in law enforcement against drivers who smoke while driving lie within the law enforcement factor because law enforcement is less strict. Community factors due to lack of public awareness of the law, facilities and infrastructure/facilities factors and cultural factors. In law enforcement efforts, there are preventive efforts carried out by the police, including providing guidance and education to the community, carrying out verbal warnings. Apart from preventive efforts, there are also repressive efforts, namely imposing sanctions on perpetrators of traffic violations using articles in Law Number 22 of 2009 concerning Road Traffic and Transportation.